What is 10/9 minus 6/9?
Looking for the result of 10/9 - 6/9? Follow this step-by-step guide to understand how to subtract these two fractions.
How to subtract 10/9 by 6/9?
- Multiply the numerator of the first term, with the denominator of the second term: 10 × 9 = 90
- Multiply the numerator of the second term, with the denominator of the first term: 6 × 9 = 54
- Subtract both of these results together to form the new numerator: 90 − 54 = 36
- Multiply both denominators together to form the new denominator: 9 × 9 = 81
- Combine the results to get the new fraction: 36/81
- Simplify the fraction (36/81) by dividing both the numerator and the denominator by their GCD (9):
- 36/9 = 4
- 81/9 = 9
- This gives: 4/9.
The result of subtracting 10/9 and 6/9 is : 4/9 (or 0.44444444444444 in its decimal form)